Education to Improve Knowledge about Free Association in Teens at SMP Satap 4 Hanau Seruyan Central Kalimantan - Eri Puji Kumalasari; Devy Putri Nursanti (Journal of Community Engagement in Health, 2025)
The community service program in Derangga Village, Pembuang Hulu District, Seruyan Regency, aims to improve the knowledge of adolescents of SMP Satap 4 Hanau about free association. In some cases, free association among adolescents in this village is starting to be worrying. The main factors that encourage free association are the lack of supervision from parents and the low level of education related to the negative impacts of this behavior. Through counseling on free association, adolescents are given an understanding of the anatomy and function of the reproductive organs, biological changes in adolescents, reproductive health problems in adolescents, free association, factors causing free sex and the consequences of free sex. The evaluation showed a significant increase in adolescent knowledge: before the counseling, only 30% of participants had good knowledge, while after the counseling, 78% of participants had good knowledge. This activity is expected to reduce the risk of health risks associated with free association, including transmission of sexually transmitted diseases (STDs) and unwanted pregnancies. This program needs to be continued with more detailed sessions and additional material support so that the knowledge gained is more in-depth and can be applied in everyday life.